Female Genital Mutilation in the UK Population: A Serious Crime. (April 2016) - Cook, Kate
This article considers the definition of female genital mutilation (FGM) in the context of United Nations work which aims to end this practice. The piece focuses on the prevalence of FGM in the UK and on legal provisions outlawing cutting in England and Wales. It argues that FGM is now relatively commonplace in the UK and ends with a call for greater public education about FGM and better support for survivors of mutilation. The article begins by looking at international ideas about FGM, drawing on knowledge from UNICEF and considering the realities of the practices carried out on young girls. It is acknowledged that there is a risk of alienating traditions that value cutting, inherent in the western view of FGM as child abuse. Nevertheless, the article argues that FGM must be eradicated. A review of information on the prevalence of FGM in UK populations follows, showing that there are many thousands of women and girl survivors now resident in Britain. FGM has been a criminal offence in England and Wales since the Prohibition of Female Circumcision Act 1985. However this legislation proved impractical and it has now been replaced by a Female Genital Mutilation Act in 2003 and that, in turn, is now amended by the Serious Crime Act 2015. An outline of the newer legislations suggests that there are signs of usefulness within the latest amendments. However the article ends with some warnings about the risks of criminalisation without appropriate levels of support and public discussion.